Early diagnosis and optimization of intraoperative management strategies for posterior tibial tendon entrapment following ankle fractures in the elderly - Yang, Shuo; Lu, Yang; Jiang, Jiliang (Vojnosanitetski pregled, 2026)
Background/Aim. Posterior tibial tendon (PTT) entrapment is a rare, often underdiagnosed, but severe complication of complex ankle fractures. The aim of the study was to determine the characteristics of PTT entrapment in elderly patients with ankle fractures, and to establish a predictive model based on preoperative available clinical and imaging data. Methods. The study enrolled a total of 130 elderly patients treated between 2019 and 2024. Data were retrospectively analyzed, and all patients completed a minimum follow-up period of 12 months. Using intraoperative confirmation as the gold standard, a basic clinical logistic regression (LR) model was compared with an imaging-enhanced LR model (incorporating fracture fragment count and PTT sheath involvement), a random forest (RF) model, and a support vector machine (SVM). Performance was validated via 5-fold cross-validation, area under the receiver operating characteristic (ROC) curve (AUC), calibration, and decision curve analysis (DCA). Results. PTT entrapment occurred in 29.2% (38/130) of patients, primarily located in the posterior fracture gap (68.4%) or medial malleolus (31.6%). Morphological findings included simple mechanical incarceration (50.0%), soft tissue adhesion (36.8%), and tendon surface injury (13.1%). The imaging-enhanced LR model significantly outperformed the basic model (AUC 0.89 vs. 0.72) and exceeded RF (0.85) and SVM (0.88) models. DCA demonstrated high net benefit across risk levels, and intraoperative findings showed high consistency with imaging-based predictions. Conclusion. PTT entrapment is common in elderly ankle fractures. An imaging-enhanced predictive model based on preoperative computed tomography fracture morphology and local anatomy enables effective risk assessment, providing a reliable reference for targeted intraoperative exploration and surgical management strategies.
Keywords: aged; ankle fractures; diagnosis; models, statistical; prognosis; tendon entrapment.